Front San Diablo na região de Miraflores – Bolívia : estratigrafia e implicações tectônica - Nedel, Ingrid Moerschberger (2016)
The study area comprises the western of the San Diablo Front (FSD), it’s a region of great importance about the SW Amazon Craton evolutionary history. Lithostructural data collected during the geological mapping (1:250,000 scale), demonstrate existence of four main lithologies in the whole area. The basis is formed by biotite gneisses metamorphosed in amphibolite facies belonging to Chiquitania Complex. Were observe in the northern and southern portions of FSD, with evidence of three distinct tectonic-metamorphic stages, indicating that the front it is a mega-structure generated inside the Land Paragua. To geochronological analyzes offered a crystallization age U-Pb (SHRIMP) from the protolith of 1685.0 ± 4.9 Ma. In disagreement to the basis, the FSD crest zone, it is shale, quartzite and metarenito from the Sunsás Group, affected by only two phases of deformation. The study about detrital zircons collected from the quartzite provided maximum age of sedimentation 1.25 Ga, and analysis from metarenito provided a maximum sedimentation age of 1.2 Ga, suggesting similar sedimentation periods, but with different sources. It was also possible to discriminate the Colmena Granite, a granitic body pre to syn-tectonic to the San Ignacio Orogeny, located on the largest deformation zone of the front, associate to mylonitization process. The data combination allowed characterize the Front San Diablo as a curvilinear transpressional shear zone with dextral character nature, related to directional/transcurrent movement with an oblique component, during Sunsás Orogeny at 1.0 Ga.